Persepsi pengaruh money politic dan Jaringan sosial terhadap Perilaku pemilih pada Kemenangan Pasangan Calon dr. Hj. WIDYA KANDI SUSANTI, MM dan wakilnya H. MUKH MUSTAMSIKIN, S.Ag, M.SI., (YAKIN) Studi Kasus Pemilukada kab.Kendal tahun 2010 - Faris Nadisa Rahman Drs. Turtiantoro, M.Si Drs. Susilo utomo, M.Si (Journal of Politic and Government Studies, 2013)
ABSTRACT General Election in accordance with UU No.32 th 2004, an election to elect a leader in the area directly and democratically. In the implementation of the election of the couples who often compete with winning strategies with a common strategy and not commonly used, the use of money politics and the strategies used by social network partners in an effort YAKIN peraihan support, although the use of one of the ultimate strategy of the candidates with the YAKIN using money politics is a form of violation in the administration of the election because the reward in cash or in kind so as to influence voters and fade values ​​of democracy in the election, but in fact this strategy became prevalent because people assume it is a necessity or a compensation for the support they provide. While the use of Social Networking strategy is the strategy of winning candidates in the elections by using the network of relationships, family and social relationships that exist within a society its use by political actors deliberately refers to the relationships forged in order mendapatakan a fringe benefit in the form of material and support to systems and political ideologies that are used. In this study, researchers used quantitative research methods research is used to examine the effect of a variable by using calculations or statistical tests. Locations in the study conducted in the District of Kendal, precisely in the District Boja, Kendal Town and Weleri. The sampling technique in this study using a multi stage random sampling, which determined the technique of determining a stratified sample, the sample taken through the sampling mechanism by taking samples from the level of District → District → Village / Village Residents → Pillars / Neighborhood → KK. In this study the respondents specified a number of 139 respondents from the community Boja district. Kendal Town district, sub Weleri. The selection of respondents based on the primary sampling unit so that the main focus of this study was the father or head of household male. Data retrieval techniques using primary data is through the distribution of questionnaires as the primary medium of research outcomes informnan collect. with informants while also using secondary data is to collect data with reference to written sources as supporting data. In the 2010 election Kendal district, money politics and social network variables have an influence on voting behavior in the winning pair SURE. Based on the F test shows the calculated F value of 25.312 is greater than the F table is 3.06 so that together there is the influence of money politics and social networks on voting behavior in the winning pair SURE. Judging from the regression test also proves positive influence to the influence of money politics and social networks on voting behavior in the winning pair SURE. Value of the coefficient of determination of 0.271 or 27.1%, which means that the influence of money politics and given social networks have positive and significant influence on voting behavior in the winning pair for SURE while the remaining 27.1% by 72.9% influenced by other variables . Keyword : General Election, Money Politics, Social Networking